The complete plastome sequences of nine diploid potato clones - Sai Reddy Achakkagari; Helen H. Tai; Charlotte Davidson; Hielke De Jong; Martina V. Strömvik (Mitochondrial DNA. Part B. Resources, 2021)
Potato (Solanum tuberosum L.) is the world’s fourth most important food crop and essential for global food security. The potato chloroplast genomes, the plastomes, are highly conserved and are largely studied for their maternal lineages. In this study, we assembled the complete circular plastome sequences of nine diploid potato clones, with sizes ranging between 155,296 bp and 155,564 bp. Annotation of these plastomes reveals that they each have 141 genes in a similar order. The computational chloroplast DNA typing reveals three plastid DNA types among the nine plastomes and they are grouped according to these types in the phylogeny.